Opportunities and constraints for participatory plant breeding: Farmers' seed-management strategies and their effect on pearl millet populations in Rajasthan, India - Brocke, Kirsten vom; Christinck, Anja; Weltzien, Eva (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
This paper presents information from a study on farmers' seed-management practices growing pearl millet in Rajasthan, India. It describes farmers' own crop-improvement activities in regard to yield, quality, and diversity of pearl millet, with emphasis on seed-management strategies, such as introgression of modem varieties, selection, storage, processing, exchange, and procurement. It also examines the farmers' definition of "variety" as compared to the definition used by professional plant breeders. For the Study, farmers were divided into four groups, based on their seed-management practices. Data were collected on specific trails and correlated with grain yield under different climatic conditions. The potential and constrains of farmers' practices are discussed, with emphasis on areas where researchers could concentrate on specified weaknesses that farmers' own selection practice. Cannot effectively address.